Understanding the role of memorable tourism experiences in loyalty at giant panda conservation centre, zoo Negara Malaysia - Thoo, Poh Yee; Johari, Shazali; Ismail, Mohd Hafizal; Yee, Lai Ling (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Memorable tourism experiences (MTEs) have recently emerged to become an important study for tourism destinations to compete in this rapid growing marketplace. Unlike visitors’ loyalty, it has always been a vital objective of service providers. Positive MTEs have been hypothesized for being able to develop future behavioral intentions in the visitors such as revisiting a destination. There is currently still lack of studies regarding the relationship between these two dimensions especially at Giant Panda Conservation Centre (GPCC) in Zoo Negara Malaysia which was established in year 2014. GPCC is the enclosure of the two giant pandas loaned to Malaysia by China to mark the 40th Anniversary Diplomatic Relationship between the two countries. For GPCC, loyal visitors and also new visitors are crucial as the giant pandas will be here for 10 years. Therefore, this research examines whether MTEs can affect a visitor’s loyalty at GPCC in Zoo Negara. A quantitative method was used with a sample of 217 visitors and multiple regression analysis was carried out. The results showed that MTEs have a significant relationship with visitors loyalty. In a nutshell, it is essential for GPCC’s management to increase positive visitors’ MTEs in order to increase the number of loyal visitors who will revisit GPCC and provide positive Word of Mouth to their family and friends so that they will help to attract more new visitors.